(untitled) (Research, Society and Development, 2021)
The objective of this study was to assess the impact of 10-valent pneumococcal conjugate (PCV10) vaccination on the incidence and mortality of pneumococcal meningitis in children under 5 in Brazil. A descriptive ecological, population-based quantitative study of secondary data from SINAN records for 2003-2009 and 2011-2017 and on vaccine coverage for 2011-2017 was conducted. The study was approved under permit CAAE 23629719.6.0000.5181. After PCV10 vaccine introduction, a substantial consistent reduction in incidence of and mortality rates of pneumococcal meningitis (70.33% Northeast, 69.49% Southeast) was observed across all regions of Brazil. Although the Human Development Index (HDI) improved during the study period, lethality rates remained high (North = 34.45% pre versus 40.08% post-vaccination), with no clear pattern of reduction associated with improved HDI in Brazil. In the final years of the study, a concerning decline in vaccination coverage rates was evident. Only the South (96.52%) and Mid-West (96.17%) regions attained the ≥ 95% vaccine coverage recommended by the Ministry of Health. This situation highlights the need for urgent measures to restore coverage rates and prevent recrudescence in cases and deaths associated with potentially preventable diseases.